ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), DAN BIAYA OPERASIONAL DIBANDINGKAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2017 - Wisnu Adi Wibowo; Nina Woelan Soebroto; Embun Duriany Soemarso (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2019)
This study aims to analyze the influence of Ratio Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Operational Income Cost Effect (BOPO) partially or simultaneously to Return On Assets (ROA) at Bank Umum Syariah in Indonesia., The period 2015-2017. The data used in this study obtained from the quarterly financial reports through the website. Population and sample in this research is Bank Syariah Mandiri, Bank Mega Syariah and Bank BNI Syariah. The results of hypothesis testing using multiple linear regression analysis using SPSS 16. The result of determination coefficient shows the result of 0,774 or 77,4% of variable Return On Assets (ROA) influenced by Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Operational Income Cost Effect (BOPO), the remaining 22,6% is influenced by other factors. The results of the F test or simultaneously Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Operational Income Cost Effect (BOPO) together have a significant effect on Return On Assets (ROA). While t test or partially, Operational Income Cost Effect (BOPO) have significant influence to Return On Assets (ROA) while Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) has no significant effect to Return On Assets (ROA) on Bank Umum Syariah in Indonesia Period 2015-2017.